Additional data to: A comprehensive dataset on spatiotemporal variation of microbial plankton communities in the Baltic Sea - Latz, Meike; Andersson, Agneta; Brugel, Sonia; Hedblom, Mikael; Jurdzinski, Krzysztof; Karlson, Bengt; Lindh, Markus; Lycken, Jenny; Torstensson, Anders; Andersson, Anders (Royal Institute of Technology, 2023)
Additional data to the publication 'A comprehensive dataset on spatiotemporal variation of microbial plankton communities in the Baltic Sea'.

Short description of the publication: A dataset covering spatiotemporal variation in prokaryotic and eukaryotic microbial communities and physicochemical parameters of the Baltic Sea. Between January 2019 and February 2020, 281 transect-time course samples and 65 samples for protocol testing were collected from 19 stations in the Baltic Sea, Kattegat and Skagerrak. We analysed the samples with 18S ribosomal RNA (rRNA) gene and 16S rRNA gene metabarcoding, to capture the eukaryotic and prokaryotic diversity, respectively. Complementary analyses were conducted on the same samples by the Swedish National Marine Monitoring Program: Microscopy analyses were performed on samples preserved in Lugol’s solution for phytoplankton identification, estimation of cell volumes and cell counts. Samples from nine stations were quantified for phototrophic picoplankton using flow cytometry and fluorescence microscopy. Chlorophyll-a content was assessed in the water as a proxy for total phytoplankton biomass and a range of physicochemical parameters were captured.

Additional data include:

-metadata file on metabarcoding samples with physicochemical parameters,

-data tables with: additional physicochemical data, data on phytoplankton abundance counts, biovolume and carbon biomass (from light microscopy), abundance of picoplankton (epifluorescence microscopy and flow cytometry), chlorophyll a content (these data can also be accessed through SHARKweb)

-R scripts and files associated with the 16S & 18S metabarcoding data (ASV, sequence & taxonomy table)

-table with file names of sequencing data (submitted to ENA)

-spike-in DNA sequences, added before DNA extraction for normalisation of the samples sequenced with metabarcoding

-instructions on how to access metadata through SHARKweb
Keywords: Biosecurity science and invasive species ecology; Environmental assessment and monitoring; Medical and Health Sciences; Medicin och hälsovetenskap